2017
DOI: 10.4049/jimmunol.1601516
|View full text |Cite
|
Sign up to set email alerts
|

Thymic Dendritic Cell Subsets Display Distinct Efficiencies and Mechanisms of Intercellular MHC Transfer

Abstract: Thymic dendritic cells (DC) delete self-Ag-specific thymocytes, and drive development of FoxP3-expressing immunoregulatory T cells. Unlike medullary thymic epithelial cells (mTEC), which express and present peripheral self-Ag, DC must acquire self-Ag to mediate thymic negative selection. One such mechanism entails the transfer of surface MHC-self peptide complexes from mTEC to thymic DC. Despite the importance of thymic DC “cross-dressing” in negative selection, the factors that regulate the process, and the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 40 publications
2
34
0
Order By: Relevance
“…It has been previously documented that distinct subtypes of thymic DCs vary in their capacity to acquire antigens from TECs 6,10,11,16 . Whereas CAT of TdTOM from TECs to cDC1 and cDC2 is very potent in the Foxn1 Cre ROSA26 TdTOMATO system, it is limited in the case of pDC (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been previously documented that distinct subtypes of thymic DCs vary in their capacity to acquire antigens from TECs 6,10,11,16 . Whereas CAT of TdTOM from TECs to cDC1 and cDC2 is very potent in the Foxn1 Cre ROSA26 TdTOMATO system, it is limited in the case of pDC (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…While cDC1 arise primarily in the thymus, cDC2 and pDCs originate extrathymically and then migrate to the thymic medullary region 14,15 . mTEC-derived antigens are transferred both to thymic resident cDC1 6,10 and cDC2 16,17 . Although it has been shown that the migration of cDC1 and cDC2 to the vicinity of mTECs is affected by a gradient of Xcl1 18 and Ccr2/Ccr7 ligands, respectively 19,20 , the potential involvement of other chemokines in the regulation of CAT still awaits resolution.…”
mentioning
confidence: 99%
“…Antigen transfer via trogocytosis, in which an immune synapse forms between cells to mediate intercellular transfer of proteins, has also been shown to allow for capture and presentation of MHCpeptide complexes by both APCs and non-APCs (Cone et al 1972;Joly and Hudrisier 2003;Nakayama 2014). In the thymus, peptides presented as a result of trogocytosis between DCs and mTECs is posited to aid in increasing presentation of rare thymic antigens by MHC-II (Klein et al 2009;Kroger et al 2017;Millet et al 2008). Intercellular MHC-II transfer has been shown to occur in a number of other peripheral immune cell subsets as well, including between DCs and NK cells (Nakayama 2014;Nakayama et al 2011).…”
Section: Nonconventional Pathways Of Mhc-ii Processingmentioning
confidence: 99%
“…While pDC and migratory DC specialize in the presentation of peripheral antigens, resident DCs provide immature T cells with a distinct self-antigenic repertoire. In addition, although thymic resident and migratory cDC can uptake MHC-I and MHC-II from thymic epithelial cells in a cell-contact dependent manner, this process is dependent on PI3K pathway only for CD8α + resident cDCs (40), further supporting the view that each DC subset provides a non-redundant role in antigen-presentation to T cells and in the maintenance of central tolerance.…”
Section: Thymic Tolerancementioning
confidence: 92%